Synthesis of fluorinated β-diketone analogues in multi-tens gram scale - Limanjaya,Megan (Nanyang Technological University, 2022)
Rapid growth in technologies has led to an increase in electronic device waste. The waste is forecasted to increase 3-5% yearly and an effort to recycle these electronics upon its end of useful life is very important. Some efforts made by scientist to extract the metal complexes/compound include Liquid-Liquid Extraction (LLE) method. This method is rather straightforward and utilizes simple apparatus, however, it can cause harm to the environment due to the solvents. To combat this issue, scientist is currently interested in Supercritical Fluid Extraction (SFE) method which is a green extraction method.